Analysis of influencing factors behind offensive rebounding performance in elite basketball. Issue 6 (December 2017) - Csátaljay, Gábor; James, Nic; Hughes, Mike; Dancs, Henriette
The aim of the research was to analyse the influencing factors of rebounding efficiency through observing position, activity and number of players struggling for rebounds. Rebounding situations were notated from all the games played by the best eight teams in Euroleague 2011/12. Kruskal–Wallis and Mann–Whitney tests were used to demonstrate the differences between variables and logistic regression was employed to find the most influential factor which particularly determined whether a rebound was grabbed by an offensive or a defensive player. The efficiency of offensive performance from actions started with offensive rebounds was higher than from offenses after possession change. The higher efficiency appeared mainly in the higher shooting efficiency and the higher number of forced free throws. The number of offensive players participated in rebounding was identified as the most important factor that influenced the efficiency of offensive rebounding. However the most ideal offensive rebounding was found for the active participation of three players. The lack of boxing out in defence was often notated for the observed teams which contributed the effective offensive rebounding of guards and forwards. The results of the current research support the better understanding of effective offensive rebounding and allow working out a theoretically established offensive rebounding team strategy.